Face Recognition Motorcycle Rider Registration System for Rider Data Management - Kana Saputra S; Insan Taufik; Irham Ramadhani; Putri Sasalia S; Yusfi Syawali; Dede Yusuf; Rezkya Nadilla Putri; Najwa Latifah Hasibuan; Fauzan Hafiz Harahap (Bulletin of Information Technology (BIT), 2025)
This research aims to develop a motorcycle rider registration system using facial recognition technology that can improve the efficiency of rider data management. This system is designed to identify and authenticate riders with high accuracy, thereby simplifying the registration and monitoring process. The methods used in this research include collecting rider facial data through cameras, image processing for feature extraction, and implementing a facial recognition algorithm. Testing was conducted in several locations with varying lighting conditions and viewing angles to ensure the system's robustness. The results show that the developed system is capable of achieving facial recognition accuracy of up to 95%. In addition, this system provides an intuitive user interface to facilitate the registration and data management process. With the implementation of this system, it is expected to reduce the time and costs required in managing motorcycle rider data, as well as improve safety and comfort while riding.